Seasonal and ontogenetic variation in the infection of intestinal parasites in Arctic charr (Salvelinus alpinus) and brown trout (Salmo trutta) in a subarctic lake. - Prati, Sebastian (UiT Norges arktiske universitet, 2019)
The vast majority of studies in northern lake systems have been carried out on a short-term scale, principally during spring and summer and mostly focusing on a single parasite species. There are few winter studies of fish parasites in the subarctic area, and even less regarding seasonal variations in the sub-communities of intestinal parasites in Arctic charr (Salvelinus alpinus) and brown trout (Salmo trutta). Seasonal and ontogenetic variations of intestinal parasites in Arctic charr and brown trout were therefore investigated. A total of 354 Arctic charr and 203 brown trout were sampled from the littoral habitat between June 2017 and May 2018, in lake Takvatn, northern Norway. I calculated the prevalence, mean intensity and mean abundance of all intestinal parasite species. A total of fife adult parasites taxa were found in the fish intestines. These parasites are trophically transmitted to the fish via zooplanktivory (Eubothrium salvelini, E. crassum, Proteocephalus sp.), benthivory (Crepidostomum spp. and Cyathocephalus truncatus) and piscivory (E. crassum and Proteocephalus sp.). Additionally, unencysted larvae (plerocercoids) of Dibothriocephalus spp. were recorded in the intestines of both salmonids, showing a high correlation with fish consumption. Diet was assessed using the frequency of occurence of prey items in the stomach and intestine. Intestinal parasites infections in Arctic charr displayed marked seasonal variations as a result of temporal changes in prey availability and host feeding behavior, whereas seasonal pattern in intestinal parasite infections in brown trout were mainly driven by host body size. Parasite infections increased with increasing fish size, leading to an accumulation through time of long-lived parasites, which was particularly evident in Arctic charr. Most intestinal parasites seemed to indicate the dietary preferences of Arctic charr and brown trout. Arctic charr exhibited the richest intestinal parasite community, which apparently was related to a broader dietary niche. ...